2013
DOI: 10.1530/jme-13-0085
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor α (ESR1) over-expression mediated apoptosis in Hep3B cells by binding with SP1 proteins

Abstract: Previous studies have reported that estrogen receptors (ERs) are expressed in normal human liver, chronic hepatitis, and benign hepatic tumor tissues. However, decreased expression of ERs can be observed in hepatocellular carcinoma (HCC) and the role of ERs in HCC is not fully understood. Thus, the present study aimed to investigate the molecular mechanism induced by the overexpression of ERa (ERa (ESR1)) in Hep3B cells. We first detected the induction of apoptosis in ER-negative Hep3B cells using DNA fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…An increasing number of studies have demonstrated that ESR1 may act as a tumor suppressor in various cancer types (16,19). The present study demonstrated that the expression levels of ESR1 are downregulated in HCC cell lines compared with normal liver cells.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…An increasing number of studies have demonstrated that ESR1 may act as a tumor suppressor in various cancer types (16,19). The present study demonstrated that the expression levels of ESR1 are downregulated in HCC cell lines compared with normal liver cells.…”
Section: Discussionsupporting
confidence: 60%
“…Hishida et al (18) predicted that ESR1 is a tumor suppressor gene in HCC by triple-combination array analysis. Additionally, Tu et al (19) demonstrated that ESR1 overexpression mediated apoptosis in Hep3B cells by binding with SP1 proteins. However, to the best of our knowledge, the effect of ESR1 on the metastasis of HCC cells has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported bazedoxifene as a novel inhibitor of IL‐6/GP130 protein‐protein interactions using multiple ligand simultaneously docking and drug repositioning approaches. The Hep3B liver cancer cell line, which is considered estrogen receptor negative, was used to examine whether bazedoxifene is capable of inhibiting IL‐6‐induced STAT3 phosphorylation. Our results showed that IL‐6 induced STAT3 phosphorylation on tyrosine 705 in Hep3B cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Immuno‐precipitation and immunoblotting were performed as previously described . Cell lysates were centrifuged at 12,000 g for 20 minutes and 100 μg of total protein were mixed with 2 μg of anti‐ERα, 20 µL of a protein protein G beads and the samples were rolled at 4°C for overnight.…”
Section: Methodsmentioning
confidence: 99%